Barriers to exercise and the role of general practitioner: A cross-sectional survey among people with multiple sclerosis - Correale, Luca; Martinis, Luca; Tavazzi, Eleonora; Pedullà, Ludovico; Mallucci, Giulia; Brichetto, Giampaolo; Bove, Marco; Ponzio, Michela; Borrelli, Paola; Monti, Maria Cristina; Bergamaschi, Roberto; Montomoli, Cristina (Frontiers in Neurology, 2022)
Introduction Regular exercise is strongly recommended for people with MS (pwMS), but recent studies still describe them as sedentary and insufficiently active. The purpose of this study is to identify the major barriers that prevent pwMS from exercising and underline the importance of the general practitioner (GP) in promoting an active lifestyle. Materials and methods We performed a multicenter cross-sectional study using a self-administered questionnaire among pwMS. Data about demographics, the disease, current exercise practice, barriers, previous GP's advice to practice, and motivation were collected. Results A total of 741 pwMS (age 55.6 ± 12.5 years, 66% females) completed the survey. Most responders (75.3%) did not practice any exercise. Fatigue was the most limiting factor to attending and/or starting an exercise program, followed by travel and/or moving issues, and the lack of time. Only 25.5% of participants received GP's advice to practice exercise, but 48.6% of them attended an exercise program. A greater likelihood of practice was evidenced for people that received the GP's advice than those who had not received it (OR 2.96; p < 0.001). Finally, among those who did not practice exercise but received advice from GPs, 69 out of 99 (69.7%) were motivated to start an exercise program. Conclusion Fatigue and physical issues are the main barriers to exercise for pwMS, but also other factors not related to the disease seem to be relevant, like travel issues and lack of time. Although few participants received advice to exercise from their general practitioner, his role proved effective in encouraging the practice.